The benefits and ethical issues behind the usage of genetically modified organism; comparison between paddy and rubber: a review / Nur Syazwani Mohamad - Mohamad, Nur Syazwani (Faculty of Plantation and Agrotechnology, 2018)
The fast globalization of the world economy has extended the requirement for a database of strong socio culture differences in acknowledgments, qualities and methods for thinking about roughly unused advancement in cultivating. The use of genetically modified crops being in farming's recorded is rising step by step, however there is no discussion have been made. There are various arguement that this genetically modified organism is one of ideal approach to enlighten various issues as for the sustenance world securities, environmental issues, and the bargain power of sales, however opposite side there's an ethical issues that rise as for the general population prosperity that eat up of this genetically altered life form shape in addition. In this review, we will recognize the advantages behind the utilization of genetically adjusted life form in paddy and rubber and this would build the learning about the ethical issues that may be rise behind the usage of this genetically modified organisms.